PENGARUH MOTIVASI, SELF EFFICACY, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT.BANK MUAMALAT INDONESIA KANTOR CABANG DENPASAR - Dimas Bima Anggriawan; Ida Bagus Made Widiadnya; Sapta Rini Widyawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
In the era of increasingly fierce business competition, the performance of employees is required to continue to increase. One of the steps to maintain or improve employee performance can be done by evaluating employee performance and making a series of improvements to always improve the quality of the employee so that the company grows and excels in the competition, or at least can survive. This study aims to examine and obtain empirical evidence of the effect of motivation, self-efficacy, and workload on employee performance at PT. Bank Muamalat Indonesia, Denpasar branch office. The methods used in this research are qualitative and quantitative methods. The number of samples used in this study was 45 using the saturated sampling method. Collecting data using observation, documentation and questionnaires. The data analysis technique used multiple linear regression analysis. The results showed that (1) motivation had a positive and significant effect on employee performance, (2) self-efficacy had a positive and significant effect on employee performance and (3) workload had a significant and negative effect on employee performance.